J13 Distributed neural networks associated with emotion processing are altered in premanifest Huntington's disease and correlated with genetic load. (29th August 2012) - Novak, M; Warren, J; Henley, S; Draganski, B; Frackowiak, R; Tabrizi, SJ
Abstract : Background: HD is associated with an early decline in ability to recognise emotional states in others. The pathophysiology underlying this is not fully understood; our objective was to clarify this. Disgust, anger and happiness were chosen as emotions of interest; recognition deficits have commonly been found for disgust and anger, and happiness was chosen as a contrasting positive emotion. Aims: To investigate changes in brain mechanisms of emotion recognition in premanifest HD gene carriers by using functional MRI (fMRI) to characterise neural networks involved in processing pictures of facial expressions of emotion, and to relate these findings to brain structure and markers of genetic load (CAG repeat length and probability of manifest disease onset in 5 years). Methods: 16 premanifest HD and 14 control subjects viewed pictures of facial expressions from the Ekman and Friesen series while undergoing 1.5T fMRI scanning. The Ekman 60 faces test was used to quantify emotion recognition accuracy outside the scanner and structural MRI with voxel-based morphometry was used to assess the relationship between this and regional grey matter volume. Results: Emotion processing in premanifest HD was associated with reduced neural activity for all three emotions in partially separable functional networks. The HD-associated modulation of disgust and happiness processing was negatively correlated with genetic load in distributed, largely extrastriatal networks. These effects were not driven merely by striatal dysfunction. There were no equivalent associations between brain structure and emotion recognition. The premanifest HD cohort did not have a behavioural deficit in emotion recognition relative to controls. Increased neural activity was seen in the premanifest HD subjects in response to all emotions in frontal regions of the brain. Conclusions: Both positive and negative emotion processing in premanifest HD is associated with reduced neural activity in distributed networks. Concurrent increased frontal neural activity suggests compensatory mechanisms might maintain functional ability in early stages of the disease. Overall, the pathophysiological effects of HD appear to precede the development of overt clinical symptoms and detectable cerebral atrophy.